Determining onset of significant facial pathology using dental wear and microwear texture analysis: a case study from the Middle Archaic (~5,500 BP) of Indiana. - Anna Casserly; Rebecca Van Sessen; Christopher Schmidt (Dental Anthropology Association, 2014)
Paleopathologists face complicated presentations of osteological conditions that accrued over a considerable period of ill-health. Determining the relative sequence of symptoms and how long the individual lived with them is critical to understanding disease onset and progression in the body and may help to identify a specific disease. This paper describes an atypical presentation of the dentition associated with a 5,000-year-old case of treponemal disease. This circumstance led to a cessation of macrowear, which allowed for an estimation of the age when the jaw began to profoundly deform. This paper also summarizes molar microwear texture analysis (DMTA) that was employed in order to determine if the diet of the victim prior to death was consistent with other people from the site.